Acceptance process for policemen as reflected in the characteristics of modern police (Academic Journal of Internal Affairs, 2018)
Numerous works have appeared about modern police and necessity and opportunities of modernizing. Much less publications are available about selection or application criteria for policemen. Possible reasons of that might be the relatively short past life of the police (detailed information about it hereby) and that renewals are published first of all in internal special documents and not in scientific works. There is also a shortage in (uptodate) inland literature dealing with examination of coherences between them. In this paper I am looking for answers whether there are attributes of modern police present in the current acceptance process and application criteria for policemen.
Keywords: police; selection; criteria